(untitled) (Bangladesh Journal of Nuclear Agriculture, 2023)
Jute, kenaf and mesta are prominent fibrous plants with significant industrial and nutritional value for optimization of their cultivation process can have substantial agricultural and economic implications. The study was conducted on exploring the impact of ethyl methane sulfonate (EMS) presoaking treatments on the germination and the sensitivity of fiber crops to mutagens. This research aimed to evaluate the germination potential of jute, kenaf and mesta variety using various concentrations of EMS presoaking treatments, and analyze the sensitivity and induced variability in the M1 generation. Seeds were presoaked in four different concentrations of EMS. The subsequent parameters, including germination, root length, and shoot length, were measured at three crucial growth stages: 12, 24, and 36 days after sowing (DAS). A probit analysis was conducted to determine the LD50 value, which signifies the concentration at which 50% of the population exhibits an adverse effect. Moreover, significant variances were detected in germination rates, root elongation, and shoot growth across the different presoaking treatments. The findings emphasize the sensitivity of these fibrous plants to EMS concentrations, with increasing concentrations having a detrimental effect on growth parameters. This information can be instrumental for breeders and agriculturists looking to optimize germination in these crops. Bangladesh J. Nuclear Agric, 37(2): 19-27, 2023